Decision of Informal Workers in Ownership of Employment BPJS Insurance in Makassar City - Sri Nurfiaty Jufri; Wardihan Sabar (Bulletin of Economic Studies (BEST), 2021)
Ownership of insurance for informal workers is an important part that accommodates various professions or occupations in participating in the national health insurance program for workers in Indonesia. This study aims to determine the factors that influence the ownership of BPJS Employment insurance on informal sector workers in Makassar City. This study uses quantitative methods. The number of samples is 70 informal workers in the city of Makassar with the sampling technique used is purposive sampling while the data collection techniques are observation, questionnaires and documentation. For binary logistic regression analysis method. The results of this study indicate that income and education factors have a significant effect on BPJS Employment insurance ownership for informal sector workers in the city of Makassar. Meanwhile, age and number of Family have no significant effect on BPJS Employment insurance ownership in the informal worker sector in Makassar City. Keywords: Insurance Ownership, BPJS, Informal Workers, Logistic Binner